Sociology and Catholic Social Teaching Contemporary Theory and Research. - Sharkey, Stephen R. (Lanham : Scarecrow Press, 2012)
Sociology and Catholic Social Teaching: Contemporary Theory and Research offers critical insights into a badly needed alternative vision to the alienation and cynicism that plague our political discourse. Arguing that Catholic social teaching stands as an important morally grounded framework for addressing today's pressing social problems, contributors explore the general principles and specific criteria required for both evaluating and advocating models of social improvement. This anthology is meant for advanced undergraduate and graduate students of sociology or Catholic social thought, as w.
10. Pursuing the Common Good: How Solidarity and Subsidiarity Can Work Together. Conference Introduction11. Discovering the Relational Character of the Common Good; 12. Education, Subsidiarity, and Solidarity: Past, Present, and Future; Part Three. About the Authors: Personal and Professional Reflections on Doing Sociology to Serve the Church; 13. Margaret S. Archer; 14. Pierpaolo Donati; 15. Patrick Fagan; 16. Anne Hendershott; 17. G. Alexander Ross; 18. Stephen R. Sharkey; 19. D. Paul Sullins; 20. Joseph A. Varacalli; Index
Description based upon print version of record.
Keywords: Christian sociology -- Catholic church; Church and social problems -- Catholic church; Religion; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Christian sociology -- Catholic Church; Church and social problems -- Catholic Church; Electronic books